(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
It has been revealed that the key subjects of the socio-pedagogical influence on children in the twentieth – the first half of the thirtieth of the XXth century included social workers, educators-inspectors, social teachers, social education inspectors, assistants and heads of social pedagogy offices, child welfare instructors, doctors-teachers, staff-workers of socio-legal support and minor protection departments and of various funds, centers and commissions to help children and some others that accomplished preventive, protective, educational, supporting, counseling, propa- gandistic, organizational, social and therapeutic functions. It has been established that the basic knowledge and skills of the socio-pedagogical staff of the affected period included: the knowledge of scientific methods of character research and influence on the social environment; individual means of personal development; elementary pedagogical psychology and pedagogical neurology; the theory of children’s movement; forms and methods of work of out-of-school establishments; general patterns of personal mental development; the ability to identify children in need of inter- vention and help; to carry out preventive measures and to help different categories of children; to collect useful material about children and to sci- entifically process it; to study minor children’s nature and habits, their surroundings; to develop recommendations for measures that could be applied to adolescents and some others.